Development of stand-alone DC energy datalogger for off- grid PV system application based on microcontroller - Ariffin, Mohd Ruzaimi; Shafie, Suhaidi; Wan Hasan, Wan Zuha; Azis, Norhafiz; Yaacob, Mohammad Effendy; Supeni, Eris Elianddy (UPM Press, 2022)
This article presents a microcontroller-based direct current (DC) energy data logger developed by adapting low-cost ATmega328 by measuring the PV system DC and voltage characteristics while simultaneously recording the measured value over time to compute the energy production Watt-hour (Wh). The prototype logger has been tested on a live 1 kW standalone PV system where the voltage sensor detects PV series array output voltage ranging between 0–50 VDC by a voltage divider sensing circuit. For accurate sensing of the current output measurement from the PV array, 50A ACS756 hall effect IC was integrated as the current sensor. The data was measured and saved in text format with comma-separated values (CSV) in an SD card, read using Microsoft Excel software. The liquid crystal display (LCD) showed the actual value of the recording process’s current, voltage, power, and duration in minutes. The recorded data has been compared to the standard laboratory digital multimeter for calibration manually to justify the measurement value. The error is minimized to 0.6% average by varying the constant float value in the programming code. The advantage of developing this logger is that the development cost is much cheaper than the standard commercial PV energy meter, can be reproduced for other DC application energy measurements, and easily modify the voltage and current range to suit the application. Apart from that, this logger also provides high accuracy performance, and its independent characteristic is practical for off-grid or off-site PV system use.